PERSEPSI MASYARAKAT TERHADAP MAKNA ULOS DALAM ADAT BATAK TOBA DI KECAMATAN TAMBUSAI KABUPATEN ROKAN HULU - Siahaan, Jekson Marusaha; Hambali, Hambali; Zahirman, Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is in the background of the problem that arose from the observations made by the researcher is about the meaning of Ulos in the Toba Batak customs in Tambusai sub-district of Rokan Hulu Regency. The problem formulation in this research is (1) how society perception toward ulos meaning from traditional ceremony of birth, marriage, and death (2) what factors influence the meaning of ulos. The purpose of this study is to determine the perception of society terhdap meaning ulos in adat batak toba in Tambusai district Rokan Hulu regency. This research method is descriptive qualitative. Population in research is all Toba Batak society in Tambusai sub-district Rokan Hulu Regency is 12.410 soul to determine the amount of sample then writer use Porpusive Sampling. Porpusive Sampling is a technique of taking or sampling with certain considerations with the number of samples of 30 people. Data were collected through observation, questionnaires and interviews. Based on the research results can be concluded that the meaning of ulos in the event of birth and marriage customs less in maintained high by the Toba Batak community in Tambusai District Rokan Hulu District and has undergone a change. While in the customary event of death batak toba in tambusai subdistrict did not change. Factors that affect the meaning of ulos Toba Batak customary events that exist in Tambusai District Rokan Hulu District is a factor of Knowledge, Technology and Religion. Keywords: meaning, ulos, customs